PENGARUH CITRA DESTINASI DAN DAYA TARIK WISATA TERHADAP KEPUTUSAN KUNJUNGAN WISATA GUNUNG PANDAN DI ACEH TAMIANG (STUDI KASUS PENGUNJUNG WISATA GUNUNG PANDAN) - Desi Fadhillah; Dhian Rosalina; Suri Amilia (NIAGAWAN, 2026)
This study aims to determine whether destination image and tourist attraction influence the decision to visit the Gunung Pandan tourism site in Aceh Tamiang. The study used a sample of 96 respondents selected through the accidental sampling technique. The data analysis method employed multiple linear regression analysis, t-test, F-test, and the coefficient of determination (Adjusted R²). The results of the study show the regression equation: Y = 1.090 + 0.208X₁ + 0.511X₂ + 0.028X₃. The results of the t-test indicate that destination image has a significant effect on the decision to visit Gunung Pandan tourism in Aceh Tamiang, whereas tourist attraction does not have a significant effect on the decision to visit Gunung Pandan tourism in Aceh Tamiang. The results of the F-test show that destination image and tourist attraction simultaneously have a significant effect on the decision to visit Gunung Pandan tourism in Aceh Tamiang. The coefficient of determination (Adjusted R²) is 0.652 or 65.2%, while the remaining 34.8% is influenced by other variables outside this study.